IMPROVING GRADE VIII STUDENTS™ VOCABULARY ACHIEVEMENT THROUGH CONCEPT ATTAINMENT MODEL - Harahap, Nova Jayanti; Arifin, Tina Mariany (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
Abstract The objective of this research was to discover whether the application of Concept Attainment Model could in Grade VIII students. It was conducted by applying CAR (Classroom Action Research). The subject of this study was Grade VIII B Private Junior High School (Sekolah Menengah Pertama : SMP) Swasta Prayatna Medan which consisted of 38 students. The instruments used were quantitative data (vocabulary test) and qualitative data (diary notes, interview, and observation). Based on the data analysis, it was found that the students™ score improved; it can be seen from the score in pre-test, post “test in Cycle I and post-test in Cycle II. In the orientation test, the mean of the students™ score was 59.3, in the post-test of the Cycle I was 69.5, and the mean of the students™ score of the last pos-test was 79.2. Based on the diary notes, interview, and observation, it shows that the expression and excitement of the students were also improved. It was found that teaching of vocabulary through Concept Attainment Model could improve students™ vocabulary achievement. It is suggested that English teachers apply this Concept Attainment Model as one of the alternative strategies in teaching vocabulary. Key Words : Vocabulary Achievement, Conceprt Attainment Model, Test, Data, Classroom Action Research